Characterization of the corrosion products formed on carbon steel after exposure to the open atmosphere in the Antarctic and Easter Island - Marco, J.F.; Gracia, Mercedes; Gancedo, J. R.; Martín-Luengo, María Ángeles; Joseph, G. (Corrosion Science, 2000)
The characterization of the corrosion products formed on carbon steel SAE 1070 after one year exposure to the open atmosphere in the Antarctic (polar climate) and in Easter Island (subtropical climate) has been carried out by means of transmission 57Fe Mossbauer spectroscopy. X-ray powder diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The major constituent of the rust formed in the Antarctic environment is goethite (α-FeOOH). The Antarctic samples also show the presence of a large proportion of lepidocrocite (γ-FeOOH) and small amounts of ferrihydrite and maghemite (γ-Fe2O3). In the case of the Easter Island samples, lepidocrocite is the major constituent of the corrosion layers. The rust formed under the Easter Island environment also contains large amounts of ferrihydrite and, in a lesser proportion, goethite and maghemite. (C) 2000 Elsevier Science Ltd. All rights reserved. | The characterization of the corrosion products formed on carbon steel SAE 1070 after one year exposure to the open atmosphere in the Antarctic (polar climate), and in Easter Island (subtropical climate) has been carried out by means of transmission 57Fe Moessbauer spectroscopy, X-ray powder diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The major constituent of the rust formed in the Antarctic environment is goethite (α-FeOOH). The Antarctic samples also show the presence of a large proportion of lepidocrocite (γ-FeOOH) and small amounts of ferrihydrite and maghemite (γ-Fe2O3). In the case of the Easter Island samples, lepidocrocite is the major constituent of the corrosion layers. The rust formed under the Easter Island environment also contains large amounts of ferrihydrite and, in a lesser proportion, goethite and maghemite. Financial support from the Fundación Andes (project C-10810/2), the Spanish CICYT (projects MAT93-0165 and PB96-0851) and both the CSIC and the Universidad de Chile are gratefully acknowledged.